2014
DOI: 10.1016/j.jcmg.2014.08.003
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of Myocardial Blood Flow in Absolute Terms Using 82Rb PET Imaging

Abstract: Objective To compare myocardial blood flow (MBF) and myocardial flow reserve (MFR) estimates from 82Rb PET data using ten software packages (SPs): Carimas, Corridor4DM, FlowQuant, HOQUTO, ImagenQ, MunichHeart, PMOD, QPET, syngo MBF, and UW-QPP. Background It is unknown how MBF and MFR values from existing SPs agree for 82Rb PET. Methods Rest and stress 82Rb PET scans of 48 patients with suspected or known coronary artery disease (CAD) were analyzed in 10 centers. Each center used one of the 10 SPs to analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
115
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 154 publications
(127 citation statements)
references
References 30 publications
5
115
0
Order By: Relevance
“…1 The more complex the measurement of a parameter (usually because derived from other parameters), the greater the propagation of measuring errors/biases and the lower the agreement between different techniques to measure the derived parameter (as demonstrated, for example, by the quantification of myocardial flow reserve (MFR) from 82Rb PET using 10 different software approaches in the RUBY-10 Study). 10 The take-home message: quantitative outputs of different algorithms generally correlate well, but are not interchangeable.…”
Section: Good Cross-correlation Does Not Mean Interchangeability Of Rmentioning
confidence: 99%
“…1 The more complex the measurement of a parameter (usually because derived from other parameters), the greater the propagation of measuring errors/biases and the lower the agreement between different techniques to measure the derived parameter (as demonstrated, for example, by the quantification of myocardial flow reserve (MFR) from 82Rb PET using 10 different software approaches in the RUBY-10 Study). 10 The take-home message: quantitative outputs of different algorithms generally correlate well, but are not interchangeable.…”
Section: Good Cross-correlation Does Not Mean Interchangeability Of Rmentioning
confidence: 99%
“…When highsensitivity, low dead-time list-mode scanners are available, infused activity can be 30 mCi (1,110 MBq) of 82 Rb or lower (Table 1). 3 Many of the systems in use today cannot be acquired at the high count rates necessary to perform the dynamic study in a 3D septa-retracted mode because of limitations on dead time. For these systems, it is necessary to acquire the dynamic study in the lower sensitivity 2D septa-extended mode.…”
Section: Optimizing the Protocolmentioning
confidence: 99%
“…7 In contrast, most SRM applications require the blood pool ROI be placed in the left atrium. 1,3 The location of these ROIs is crucial in obtaining accurate blood flow measurement, and technologists must be trained on appropriate processing techniques. 8 …”
Section: Processingmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, in one of the largest studies by Nesterov et al, a multicenter study comparing all existing software packages (N = 10) for the quantification of Rb-82 PET myocardial perfusion imaging, the authors concluded that when using the identical kinetic model, software solutions might be interchangeable. 14 While most such studies focused on the comparison of software packages in patients that were assessed for coronary artery disease in a daily clinical routine manner, the present manuscript focused on a certain subpopulation with structural changes of the left ventricular geometry, namely patients suffering from hypertrophic cardiomyopathy. This disease entity is the most common genetic cardiovascular disease in the general population and is therefore of daily importance in a cardiovascular imaging center.…”
mentioning
confidence: 99%